Three Phases of Human Development Index Towards Global Common Stewardship Based on Environmental Kuznets Curve - Riyono, Kenley Maccauley; Widianingsih, Luky Patricia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to examine the effect of economic development (represented as the human development index) on environmental degradation (represented as global commons stewardship) with income level phase separation based on the Environmental Kuznets Curve to find out whether there is environmental policy during economic development. Environmental degradation is one of the urgent problems that must be addressed before it is too late. Every country should have a more environmentally oriented outlook apart from economic development. The research model test was carried out using multiple linear regression methods in STATA. The results of the study show that no country has succeeded in having a good environmental level with high economic development. Environment policy needs to be implemented in every country to maintain the ecosystems on earth during economic development. So far, it is evident that each country has paid little attention to its surrounding environment and has only focused on economic development.